Desenvolvimento de Azadirachta indica A. Jussieu submetida a diferentes níveis de nitrogênio na região Oeste do Estado de São Paulo - Mano, Kátia Regina (2006)
The neem tree (Azadirachta indica A. Jussieu) is an exotic tropical tree that has been studied because its gets azadiractin (AZ) an important active principle with medicinal and insecticide properties. However its forestry characteristics and its handling are few known, so this work comes to contribute with the knowledge of this specie. This work was carried out at west region of São Paulo state. The treatments were six nitrogen rates of urea corresponding at 0; 9; 18; 27; 36; e 45 g of N*plant-1. The experimental design was a randomized blocks with six treatments and five repetitions with four plants per fragment. The characteristics evaluated were: height of tree, Diameter at Breast Height (DBH at 1,30 m from soil) and Diameter at Lap Height (DLH at 0,05 m from soil) The evaluation system to collect measures was in a permanent plot system. There were no statisticals differences among the treatments at 5% of significance.